1992
DOI: 10.1073/pnas.89.23.11490
|View full text |Cite
|
Sign up to set email alerts
|

Brain proteins in plants: an Arabidopsis homolog to neurotransmitter pathway activators is part of a DNA binding complex.

Abstract: The G box is a well-characterized cis-acting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(178 citation statements)
references
References 44 publications
10
168
0
Order By: Relevance
“…Since these assays are carried out under non-denaturing conditions, it is possible that additional, negatively charged proteins are associated with GBF in the nuclear extract such that a faster migrating complex is formed. We note that the previously described GF14 protein that appears to be associated with GBF is highly acidic (de Vetten et al, 1992).…”
Section: Binding-site Sequence Specificity Of Gbf Imentioning
confidence: 56%
See 1 more Smart Citation
“…Since these assays are carried out under non-denaturing conditions, it is possible that additional, negatively charged proteins are associated with GBF in the nuclear extract such that a faster migrating complex is formed. We note that the previously described GF14 protein that appears to be associated with GBF is highly acidic (de Vetten et al, 1992).…”
Section: Binding-site Sequence Specificity Of Gbf Imentioning
confidence: 56%
“…A specific DNA-protein complex was formed with extracts from E.colicarrying the GBF1 expression vector, and that complex was effectively competed when the dyad G-box oligonucleotide was included in the binding reaction ( Figure 6b, lanes 2 and 3). No complexes were formed with control E. coil protein extracts from cells carrying pET-GF14 (lanes 4 and 5), suggesting that bacteria have no proteins with G-box binding affinity in this assay and demonstrating further that GF14 protein is not a G-box DNA binding factor in and of itself (de Vetten et aL, 1992).…”
Section: Binding-site Sequence Specificity Of Gbf Imentioning
confidence: 83%
“…A monoclonal antibody raised against GF14, a 14-3-3 protein from A. thaliuna [18], demonstrated the existence of 14-3-3 homologs in both, the soluble and the microsomal, fractions from leaves of C. communis. The antibody exclusively recognized a doublett of polypeptides of approximately 31 and 32 kDa in those crude fractions, confirming its specificity and applicability for C. communis (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblot analysis was carried out as in [17]. The monoclonal antibody raised against GF14 [18], a 14-3-3 protein from A. thaliana (antibody GF14-19, kindly provided by Dr. R.J. Ferl, Gainesville, USA), was used at a final dilution of 1: 5,000. The antiserum against the A. thaliana H'-ATPase was kindly provided by Dr. R. Serrano, Valencia, Spain, and was used at a final dilution of l:lO,OOO.…”
Section: Methodsmentioning
confidence: 99%
“…In these non-mammalian species, a variety of roles for regulation of gene expression have been suggested, (reviewed in [4]). More recently, additional evidence for a role in regulation of transcription has come from the group of Ferl [17] who have shown that a plant 14-3-3 homologue binds to the G-box promoter element of inducible genes. In some mammalian tissues, novel isoforms may be expressed at high level.…”
Section: Introductionmentioning
confidence: 99%